Diagnostic performance of an immunoassay for simultaneous detection of HCV core antigen and antibodies among haemodialysis patients - El-Emshaty,Wafaa M (2011)
Nosocomial transmission of HCV is a concern in haemodialysis (HD) units worldwide. Diagnosis of HCV infection among dialysis patients is currently based on the detection of anti HCV antibodies by ELISA, and is confirmed by HCV RNA. The average window period between HCV infection and seroconversion with new generations of HCV antibody tests remains approximately 70 days with more prolonged period among dialysis patients. In this study we assessed the diagnostic performance of an immunoassay designed for simultaneous detection of anti HCV antibodies and core antigen in one step in comparison to qualitative RT-PCR and anti HCV antibodies detection test among Egyptian haemodialysis patients. The studied patients were 39 chronic renal failure patients on maintenance haemodialysis. The results obtained in the present study revealed HCV infection of 56.4%. Combined Ag/Ab test detected 3 out of the 4 anti-HCV negative viraemic patients who were in the window period. The sensitivity, specificity and accuracy of the test were higher than that of anti HCV antibodies detection test (95.45%, 94.1% and 94.87% versus 81.8%, 88.23% and 84.6%) and they were raised to 100% on combining its positivity with liver enzymes elevation results. Therefore, this simple combined Ag/Ab test can be applied for early detection of HCV infection during window period among HD patients as an alternative to HCV RNA detection.